2016
DOI: 10.15171/joddd.2016.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Orthokin, Sensikin and Persica mouth rinses on the force degradation of elastic chains and NiTi coil springs

Abstract: Background. Elastomeric chains and NiTi coil springs are two major traction aids in orthodontic tooth movements. Force degradation occurs over time in both groups, with higher percentages in elastic chains. The effects of environmental factors and some mouth rinses on this force decay have been previously studied. No study has been performed to evaluate the effect of current popular mouth rinses such as Orthokin, Sensikin and Persica on this force degradation.Methods. Forty pieces of elastic chains consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 21 publications
2
34
0
1
Order By: Relevance
“…In the literature, multiple studies have been conducted with the purpose of analyzing elastomeric chains. As it appears, after thoroughly analyzing multiple studies regarding the biomechanical properties of elastomeric chains, results show ver y different values of force degradation in the same way as archwires [7,23]. Some authors reported that received coated archwires have significantly lower values of ultimate tensile strength and modulus of elasticity when compared to the as received regular NiTi wires [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, multiple studies have been conducted with the purpose of analyzing elastomeric chains. As it appears, after thoroughly analyzing multiple studies regarding the biomechanical properties of elastomeric chains, results show ver y different values of force degradation in the same way as archwires [7,23]. Some authors reported that received coated archwires have significantly lower values of ultimate tensile strength and modulus of elasticity when compared to the as received regular NiTi wires [26].…”
Section: Resultsmentioning
confidence: 99%
“…Of course, force decay may be influenced by factors like temperature and pH levels. It has been demonstrated that in vitro, simulating an oral environment with a basic pH level of 7.26, force decay occurs more rapidly than in an acidic pH level of 4.95 or in air [7,11,23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Although the main feature of these chains is to return to their original length to exert force, several studies have demonstrated reduction of their force following in vivo and in vitro usage. [1][2][3][4] Several factors including primary stretch, experiment environment, pH, temperature, design of chains, and manufacturer (commercial brand) could influence force decay of elastomeric chains. 1,[5][6][7] Another influencing factor is mouthwash which is used by the patients during orthodontic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, some investigators assessed the effect of sodium fluoride mouthwash on force decay of elastomeric chains. 4,[8][9][10] However, there is a controversy among the results of these studies. Some reported significant force decay following immersion of chains in sodium fluoride mouthwash, 9,10 while others revealed no effect of this mouthwash on force decay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation